NEA v. Finley: A Decision in Search of a Rationale - Lackland H.,Jr. Bloom (Washington University Law Quarterly, 1999)
For the better part of a decade, debate has raged over whether Congress can constitutionally restrict, or at least influence, the ability of the National Endowment for the Arts (“NEA”) to award grants to artists and institutions for the creation or display of art work that a significant segment of the public would consider highly offensive. In the October 1997 Term, the Supreme Court, by an 8-1 margin in NEA v. Finley, upheld section 954(d), a 1991 congressional amendment to the NEA Act that requires the Chairperson of the NEA to ensure that, in establishing regulations and procedures for assessing artistic excellence and artistic merit, “general standards of decency and respect for the diverse beliefs and values of the American public” are taken into consideration. This Article analyzes the opinions in Finley, speculates on the significance of the case, and suggests an alternative rationale for the decision that has both advantages and disadvantages over the Court’s opinion. Part II provides a brief history of the arts funding controversy and the Finley litigation. Part III examines the three opinions in Finley, relying heavily on the incisive critiques of the majority opinion developed by Justices Scalia and Souter. Part IV discusses the dynamics of the Finley opinion as an exercise in Supreme Court decision making. Part V considers the doctrinal impact of Finley on viewpoint discrimination and the unconstitutional conditions doctrine. Finally, Part VI offers a doctrinal rationalization of Finley that I believe better captures the essence of the controversy in Finley and considers whether that rationalization would have been a preferable approach.
Keywords: Grants in aid (Public finance); Law & art; Obscenity (Law); National Endowment for the Arts; Freedom of speech; Government aid to the arts; NEA v. Finley; 118 S. Ct. 2168 (1998)